2019
DOI: 10.1177/0954407019875296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydraulic flow rate, injection timing, and exhaust gas recirculation on particulate and gaseous emissions in a light-duty diesel engine

Abstract: Nozzle hydraulic flow rate is a critical parameter that affects the combustion process and plays a vital role in the production of emissions from a diesel engine. In this study, injection characteristics, such as normalized injection rate and spray tip penetration, were analyzed for different hydraulic flow rate injectors with the help of spray experiments. To further investigate the effects of hydraulic flow rate on engine-out particulate and gaseous emissions, engine experiments were performed for different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Lowering the EGR rate and advancing the SoI timing reduce PM emissions (Figure 4). 99 However, their effects on PM reduction are reduced by decreasing the hydraulic flow rate (HFR; the volume of fuel flow per unit time) due to improved fuel-air mixture strength. Lower compression ratio (CR) engines emit higher PM than higher CR engines (Figure 5).…”
Section: Particulate Emissions Overviewmentioning
confidence: 99%
“…Lowering the EGR rate and advancing the SoI timing reduce PM emissions (Figure 4). 99 However, their effects on PM reduction are reduced by decreasing the hydraulic flow rate (HFR; the volume of fuel flow per unit time) due to improved fuel-air mixture strength. Lower compression ratio (CR) engines emit higher PM than higher CR engines (Figure 5).…”
Section: Particulate Emissions Overviewmentioning
confidence: 99%
“…Hydraulic nozzle flowrate has been broadly studied in diesel engines, finding that a reduction in flowrate can have beneficial effects on soot formation and NOx. 25,26 Rollbusch 27 found that a lower hydraulic flowrate can promote less soot by means of a higher mean relative air-to-fuel ratio at medium loads, while the same effect was not present at full loads. Reducing hole diameter in the nozzle can affect the local mixing rate, which translates into better gas entrainment that can be associated with lower fuel consumption.…”
Section: Introductionmentioning
confidence: 99%